Clinical, instrumental, serological and histological findings suggest that hemophilia B may be less severe than hemophilia A - Melchiorre, D.; Linari, S.; Manetti, M.; Romano, E.; Sofi, F.; Matucci-Cerinic, M.; Carulli, C.; Innocenti, M.; Ibba-Manneschi, L.; Castaman, G. (Haematologica (Roma), 2016)
Recent evidence suggests that patients with severe hemophilia B may have a less severe disease compared to severe hemophilia A. To investigate clinical, radiological, laboratory and histological differences in the arthropathy of severe hemophilia A and hemophilia B, 70 patients with hemophilia A and 35 with hemophilia B with at least one joint bleeding were consecutively enrolled. Joint bleedings (<10, 10-50, >50), regimen of treatment (prophylaxis/on demand), World Federation of Hemophilia, Pettersson and ultrasound scores, serum soluble RANK ligand and osteoprotegerin were assessed in all patients. RANK, RANK ligand and osteoprotegerin expression was evaluated in synovial tissue from 18 hemophilia A and 4 hemophilia B patients. The percentage of patients with either 10-50 or more than 50 hemarthrosis was greater in hemophilia A than in hemophilia B (P<0.001 and P=0.03, respectively), while that with less than 10 hemarthrosis was higher in hemophilia B (P<0.0001). World Federation of Hemophilia (36.6 vs. 20.2; P<0.0001) and ultrasound (10.9 vs. 4.3; P<0.0001) score mean values were significantly higher in hemophilia A patients. Serum osteoprotegerin and soluble RANK ligand were decreased in hemophilia A versus hemophilia B (P<0.0001 and P=0.006, respectively). Osteoprotegerin expression was markedly reduced in synovial tissue from hemophilia A patients. In conclusion, the reduced number of hemarthrosis, the lower World Federation of Hemophilia and ultrasound scores, and higher osteoprotegerin expression in serum and synovial tissue in hemophilia B suggest that hemophilia B is a less severe disease than hemophilia A. Osteoprotegerin reduction seems to play a pivotal role in the progression of arthropathy in hemophilia A.